A framework of management tools for cooperation in distribution networks. (2019) - Verschoore, Jorge Renato; Storck, Theo
Business networks have emerged as a strategic model that assigns excellence and competitiveness. Despite its popularity, literature indicates the management of network cooperation as a knowledge gap. The main objective of this paper is to propose a framework of management tools for cooperation in distribution networks. To do so, four management tools were considered: contractual, strategic, decision and integration tools. This is a qualitative research based on a case study of a multinational company belonging to an American industrial group. We made semi-structured interviews and a focus group with members of the company and its sales representatives. Backed on academic literature and empirical data, we present the main elements of the four tools in the context of distribution networks and organise them into a framework to support management decisions. Our results are linked to this specific case in a particular context that allows an in-depth study but not the enlargement of the empirical field. Future studies could aim at other business networks and address additional management tools.